Inheritance of juvenile resistance to powdery mildew in barley accessions from Ethiopia - R. A. Abdullaev; O. V. Yakovleva; T. V. Lebedeva (Труды по прикладной ботанике, генетике и селекции)
Background. Barley (Hordeum vulgare L.) is one of the key food crops, ranking fourth in the world in terms of sown area and production among cereals. Often, one of the main factors that reduces yield and product quality is the spread of fungal pathogens in commercial crops. Powdery mildew (causative agent: Blumeria graminis (DC.) Golovin ex Speer f. sp. hordei Marchal) is considered one of the most common and harmful among barley diseases. Plant resistance to B. graminis limits the spread of the disease, and the development of resistant cultivars prevents a decrease in plant productivity. The specificity of the host–pathogen relationship and the loss of efficiency in many genes determine the need for a continuous study of previously unexplored local barley forms and a search for new, most effective resistance genes.Materials and methods. The genetic control of juvenile resistance to B. graminis was studied in 14 accessions of spring barley from the Ethiopian (Abyssinian) center of crop origin. The natural population of the pathogen served as infectious material for infecting barley. The intensity and nature of sporulation as well as the qualitative reactions of plant tissues in response to the penetration of the fungus (necrosis and chlorosis) were accepted as indicators of resistance in the accessions. Powdery mildew resistance was assessed under laboratory and field conditions. The genetic control of the resistance trait was studied using the method of hybridological analysis followed by statistical processing.Results and conclusions. Barleys from the Ethiopian center of morphogenesis are characterized by great genetic diversity. Studying the inheritance of juvenile resistance to powdery mildew made it possible to ascertain the monogenic control of the trait in all studied forms. Ten barley accessions with one effective recessive resistance allele and four with the dominant control of the trait may be recommended for immunity-targeted breeding.